Class inequality in austerity britain : power, difference and suffering - Atkinson, Will; Roberts, Steven; Savage, Mike (Hampshire, England Palgrave MacMillan, 2012)
This volume dissects how the economic crisis and recession of the late 2000s and the subsequent austerity measures of the coalition government have impacted on class inequalities in the UK.
Keywords: Desigualdad económica; Crisis económicas -- Gran Bretaña